2024
DOI: 10.1590/s1677-5538.ibju.2024.0017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical safety and efficacy of microwave ablation for small renal masses

Ashley Foret,
Christopher B. Haaga Jr.,
Shivani Jain
et al.

Abstract: Purpose: CT-guided MWA is a safe and eff ective tool that should be utilized in the treatment of small renal masses (SRMs). We aim to clarify the utility of CT-guided MWA by examining patient outcomes such as recurrence, treatment success, changes in renal function, and complications.Methods: A retrospective review of consecutive patients with SRMs who underwent same day renal mass biopsy (RMB) and CT-guided MWA between 2015 and 2022 was performed.Treatment safety was assessed by 30-day complications according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The group of Dr. Westerman performed in page 227 ( 9 ) a nice study about the clinical safety and efficacy of microwave ablation (MWA) for small renal masses (SRMs) and concluded that these findings support the utility of CT-guided MWA as a tool for treatment of SRMs.…”
mentioning
confidence: 99%
“…The group of Dr. Westerman performed in page 227 ( 9 ) a nice study about the clinical safety and efficacy of microwave ablation (MWA) for small renal masses (SRMs) and concluded that these findings support the utility of CT-guided MWA as a tool for treatment of SRMs.…”
mentioning
confidence: 99%